Il Cratere: la riscrittura del reale come azione credibile e sempre leggibile - Aiello, Emiliano (Scenari, 2021)
Il Cratere is a movie by Silvia Luzi and Luca Bellino that deals with the theme of the father/daughter relationship through a new filmic reading of reality. In this essay, starting from the vision and analysis of the movie, we want to tackle the theme of the staging of reality through acting. When this allows every action of the actors, to be credible and at the same time readable? There is a fundamental choice in the two authors to show a partiality for the whole. Also through the choice of the way to shot. Starting from the reading of the everyday it is possible to represent a world that, closed in their home, becomes claustrophobic as a place of imprisonment, from which there is always a possibility of escape.